2019
DOI: 10.1038/s41598-019-52903-1
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Methylation Epimutation Biomarkers for Male Infertility and FSH Therapeutic Responsiveness

Abstract: Male factor infertility is increasing and recognized as playing a key role in reproductive health and disease. The current primary diagnostic approach is to assess sperm quality associated with reduced sperm number and motility, which has been historically of limited success in separating fertile from infertile males. The current study was designed to develop a molecular analysis to identify male idiopathic infertility using genome wide alterations in sperm DNA methylation. A signature of differential DNA meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 37 publications
(52 reference statements)
1
37
1
Order By: Relevance
“…A strong association has been reported between aberrant sperm DNA methylation and male infertility (Darbandi et al, 2019). Studies have shown that germ cell-specific DNA methylation aberrations might result in oligozoospermia, abnormal sperm morphology and decreased progressive sperm motility (Gunes, Agarwal, et al, 2018;Lujan et al, 2019). In oligozoospermic men, the maternally imprinted MEST gene DNA methylation was found to be significantly associated with elevated serum FSH levels and decreased testicular volume (Klaver et al, 2013).…”
Section: Methylation Characteristicsmentioning
confidence: 99%
“…A strong association has been reported between aberrant sperm DNA methylation and male infertility (Darbandi et al, 2019). Studies have shown that germ cell-specific DNA methylation aberrations might result in oligozoospermia, abnormal sperm morphology and decreased progressive sperm motility (Gunes, Agarwal, et al, 2018;Lujan et al, 2019). In oligozoospermic men, the maternally imprinted MEST gene DNA methylation was found to be significantly associated with elevated serum FSH levels and decreased testicular volume (Klaver et al, 2013).…”
Section: Methylation Characteristicsmentioning
confidence: 99%
“…Similarly, DNA methylation-mediated wide genomic imprinting is frequently altered in men with oligoasthenoteratozoospermia and oligozoospermia [ 129 , 130 ]. A molecular analysis of genome wide alterations in sperm DNA methylation has been used to identify male idiopathic infertility, being also responsive to follicle stimulating hormone (FSH) therapeutic approach [ 131 ].…”
Section: Epigenetic Signature Of Male Germlinementioning
confidence: 99%
“…Interestingly, toxicants also change DNA methylation status in sperm [ 210 ], at the level of paternally imprinted genes [ 211 ]. Abnormalities in the sperm’s nucleus due to altered DNA methylation are, indeed, one of the primary sources of environmental exposure-dependent male infertility [ 131 ]. Human genome includes a high percentage of long-interspersed nucleotide elements (LINE-1) which are heavily methylated in normal conditions; BPA exposure specifically influences LINE-1 methylation in SPZ [ 212 ].…”
Section: Epigenetic Mechanisms Are Sensitive To Environment and LImentioning
confidence: 99%
“…Another new and interesting line of investigation by Luj an et al (5) has involved the use of sperm DNA methylation patterns to identify potential responsiveness to FSH therapy. These investigators developed a molecular diagnostic study to determine genomewide alterations in sperm DNA methylation patterns that might categorize patients as being either responsive or nonresponsive to FSH therapy.…”
mentioning
confidence: 99%
“…Furthermore, they found that DMR results could be used to efficiently separate FSH therapy responders from nonresponders and concluded that their work serves as one of the first proof-of-principle studies that a therapeutic epigenetic biomarker could be developed. The investigators concluded their work by calling for the initiation of further studies, including clinical trials, to both validate and apply this new technology (5).…”
mentioning
confidence: 99%